2005
DOI: 10.1182/blood-2004-11-4394
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length as a prognostic parameter in chronic lymphocytic leukemia with special reference to VH gene mutation status

Abstract: B-cell chronic lymphocytic leukemia (CLL) consists of 2 prognostic entities where cases with mutated immunoglobulin V H genes have better outcome than unmutated cases. V H -mutated CLLs display longer telomeres compared with unmutated cases and telomere length has been indicated to predict outcome, although the prognostic value of telomere length has not been fully established in CLL. We analyzed telomere length, V H gene mutation status, and clinical parameters in a large series of CLL. Telomere length was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
81
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 47 publications
17
81
1
7
Order By: Relevance
“…In the search for additional predictors of CLL prognosis, a number of genetic and biochemical markers have been proposed. These include determinations of CD38 surface expression [21,[44][45][46], chromosomal abnormalities [24,47,48], telomere length [49], and thymidine kinase expression [50][51][52]. The utility of certain biological markers, e.g., CD38 [23,24,44] and chromosomal abnormalities [46,48] may be unreliable and/or compromised by instability during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for additional predictors of CLL prognosis, a number of genetic and biochemical markers have been proposed. These include determinations of CD38 surface expression [21,[44][45][46], chromosomal abnormalities [24,47,48], telomere length [49], and thymidine kinase expression [50][51][52]. The utility of certain biological markers, e.g., CD38 [23,24,44] and chromosomal abnormalities [46,48] may be unreliable and/or compromised by instability during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…22 On the basis of these premises, it is not surprising that TL bears independent prognostic value in CLL. 28,29 Previous studies have shown that TL associates with IGHV homology, high-risk cytogenetics and poor TFS. 25,26 Subsequent reports outlined the existence of patients in which discordance exists between TL and IGHV-MS and suggested a superior predictive value of TL.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Although early studies postulated that telomere length (TL) was mostly acting as a surrogate marker for IGHV-MS, a number of subsequent reports indicated that in discordant cases TL performed better than IGHV-MS, suggesting that TL deserved further consideration as a prognostic biomarker in CLL. 28,29 Despite these encouraging results, additional experience needs to be accumulated on TL as a prognostic marker in CLL. First, a larger patient sample is required to establish the prognostic role of TL fully, define the optimal cutoff value and confirm results in a blinded validation series.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was evaluated in an earlier study from our laboratory 33 showing a significant correlation with Southern blot results. Several modifications to the original protocol were included in the present study and the following primers were used: tel 1b CGGTTTGTTTGGGTTTGGGTTTGG GTTTGGG TTTGGGTT; tel 2b GGCTTGCCTTA-CCCTTAC CCTTACCCTTACCCTTACCCT;HBG3:TGTGCTGGCCCAT CACTTTG; HBG4: ACCAGCCACCACTTTCTGATAGG.…”
Section: Telomere Length Determination By Quantitative Real-time Pcrmentioning
confidence: 99%